The remarkable phenotypic variability of the p.Arg269HiS variant in the TRPV4 gene. Issue 1 (26th October 2018) - Jędrzejowska, Maria; Dębek, Emilia; Kowalczyk, Bartłomiej; Halat, Paulina; Kostera‐Pruszczyk, Anna; Ciara, Elżbieta; Jezela‐Stanek, Aleksandra; Rydzanicz, Małgorzata; Gasperowicz, Piotr; Gos, Monika
ABSTRACT: Introduction : Mutations in the TRPV4 gene are associated with neuromuscular disorders and skeletal dysplasias, which present a phenotypic overlap. Methods : Next‐generation sequencing and Sanger sequencing were used to analyze the TRPV4 gene. Results : We present 2 Polish families with TRPV4 ‐related disorder harboring the same p.Arg269His mutation. The disease phenotypic expression was extremely variable (from mild scapular winging to severe hypotonia, global weakness, inability to walk unaided, congenital contractures, scoliosis, and respiratory insufficiency), but did not suggest anticipation. The 2 most severely affected patients showed congenital distal contractures of the upper limbs and involvement of cranial nerves (manifesting as facial asymmetry and strabismus). The disease course seemed to be stable, although in later stages it caused respiratory insufficiency and progression of physical disability. Discussion : The phenotypic variability observed in p.Arg269His carriers suggests that an additional modifier or a more complex pathogenic mechanism exists. Muscle Nerve 59 :129–133, 2019